Upaya Pembuktian oleh Aparat Penegak Hukum dalam Rangka Mencari Kebenaran Materiil Dalam Perkara Pidana Cyber crime - Gineng, Pratidina; , Dr. Natangsa Surbakti, S.H., M.Hum (2017)
The era of globalization is also becoming more sophisticated information technology that has affected the emergence of various forms of crime that are modern, more impact than a conventional crime. Modern is defined as the sophistication of the crime so that the disclosure was by means phisticated as well. In the crime of cybercrime, particularly in mputers and computer programs, this evidentiary problems become an important part, but also difficult. To prove, whether the defendant is guilty, or to search for material truth, the needed evidence before the court. Proof is an absolute requirement to provide assurance to the judge in order to provide decision could give the fairest decision.Keywords: globalization, cybercrime, evidence.